Enhanced proliferation of oligodendrocyte progenitor cells following retrovirus mediated Achaete-scute complex-like 1 overexpression in the postnatal cerebral cortex in vivo - Galante, Chiara; Marichal, Nicolás; Scarante, Franciele Franco; Ghayad, Litsa Maria; Shi, Youran; Schuurmans, Carol; Berninger, Benedikt; Péron, Sophie (Frontiers in Neuroscience, 2022)
The proneural transcription factor Achaete-scute complex-like 1 (Ascl1) is a major regulator of neural fate decisions, implicated both in neurogenesis and oligodendrogliogenesis. Focusing on its neurogenic activity, Ascl1 has been widely used to reprogram non-neuronal cells into induced neurons. In vitro, Ascl1 induces efficient reprogramming of proliferative astroglia from the early postnatal cerebral cortex into interneuron-like cells. Here, we examined whether Ascl1 can similarly induce neuronal reprogramming of glia undergoing proliferation in the postnatal mouse cerebral cortex in vivo. Toward this goal, we targeted cortical glia during the peak of proliferative expansion (i.e., postnatal day 5) by injecting a retrovirus encoding for Ascl1 into the mouse cerebral cortex. In contrast to the efficient reprogramming observed in vitro, in vivo Ascl1-transduced glial cells were converted into doublecortin-immunoreactive neurons only with very low efficiency. However, we noted a drastic shift in the relative number of retrovirus-transduced Sox10-positive oligodendrocyte progenitor cells (OPCs) as compared to GFAP-positive astrocytes. Genetic fate mapping demonstrated that this increase in OPCs was not due to Ascl1-mediated astrocyte-to-OPC fate conversion. Rather, EdU incorporation experiments revealed that Ascl1 caused a selective increase in proliferative activity of OPCs, but not astrocytes. Our data indicate that rather than inducing neuronal reprogramming of glia in the early postnatal cortex, Ascl1 is a selective enhancer of OPC proliferation.